2005
DOI: 10.1080/14017430510035916
|View full text |Cite
|
Sign up to set email alerts
|

Deep endometriosis, including intestinal involvement – the interdisciplinary approach

Abstract: Deep endometriosis is a disease which may involve all organs of the pelvis. The lesion is most often located at the backside of the uterus, involving the uterosacral ligaments and/or the rectovaginal septum. The involvement of adjacent organs, e.g. bowel, ureter, and bladder, makes an interdisciplinary approach necessary. There is a correlation between the radicalness of endometriosis resection and the postoperative improvement of complaints. In a series of 202 patients with deep endometriosis including the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 16 publications
3
67
0
3
Order By: Relevance
“…When they compared these results to those obtained after laparotomic colorectal resection, they found a similar rate of complications [51]. Keckstein and Weisinger [25] found a 7.4% complications rate and Daraï et al [26] reported a 10% complications rate, with 6% being rectovaginal fistulas. When the laparotomic approach is used, Dousset et al [5] reported a 16% complications rate, with 4% being rectovaginal fistulas.…”
Section: Radical Surgery With Intestinal Resectionmentioning
confidence: 62%
See 3 more Smart Citations
“…When they compared these results to those obtained after laparotomic colorectal resection, they found a similar rate of complications [51]. Keckstein and Weisinger [25] found a 7.4% complications rate and Daraï et al [26] reported a 10% complications rate, with 6% being rectovaginal fistulas. When the laparotomic approach is used, Dousset et al [5] reported a 16% complications rate, with 4% being rectovaginal fistulas.…”
Section: Radical Surgery With Intestinal Resectionmentioning
confidence: 62%
“…There were also five nonsystematic revisions published [3,28,[32][33][34]. In some of the studies, a radical treatment was assessed [5,13,15,[25][26][27][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56], while others assessed a conservative one [57][58][59][60][61][62][63]. There were six nonrandomized papers in which groups of patients with different therapeutic options were compared [30,[35][36][37][38][39].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lately, there has been a great deal of effort to advocate shaving as the treatment of choice, mainly because of higher early and late complications in segmental colorectal resection [36]. The efficacy of segmental colorectal resection is very debatable; data in this regard is controversial and, to a great deal, dependent upon the surgeon's experience [37,38]. Findings from histopathologic analysis of specimens from segmental bowel resection indicates that in 50% of cases there is a satellite lesion independent of the primary deep nodule.The deepest layer of the bowel wall containing endometrioticfoci at the primary lesion is in the submucosal layer in 70% of cases and the internal circular muscle layer in 30%.…”
Section: /6mentioning
confidence: 99%